Pemberian Reward dalam Pembelajaran dan Peningkatan Motivasi Belajar Siswa Sekolah Dasar di Kota Cirebon - Marina Luksiana Azhan; Anggianita Putri Wulandari; Fuji Afriani; Suherli Kusmana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Learning motivation is a key factor that plays an important role in supporting the success of the learning process of elementary school students. High learning motivation encourages students to actively engage in learning activities, persist in completing tasks, and strive to achieve optimal learning outcomes. However, empirical conditions indicate that the learning motivation of elementary school students in Cirebon City remains relatively low. This situation highlights the need for appropriate instructional strategies that are able to provide positive reinforcement to students. One strategy that can be implemented is the provision of rewards in the learning process as a form of appreciation for students’ positive learning behaviors and efforts. This study aims to examine the relationship between the implementation of rewards in learning and the learning motivation of elementary school students in Cirebon City. The research employed a quantitative approach with a correlational research design. The research subjects consisted of fifth-grade students from three elementary schools, namely SDN 1 Karang Jalak, SDN 1 Kedawung, and SDN Kalijaga Permai. Data were collected using a Likert-scale questionnaire that included indicators of reward implementation and student learning motivation. The collected data were analyzed descriptively using percentage analysis to describe the tendency of each variable. The results indicate that schools with higher levels of reward implementation tend to have higher levels of student learning motivation. Nevertheless, the findings also reveal that learning motivation is not solely influenced by rewards, but is also affected by other factors such as students’ intrinsic motivation, teacher support, learning environment, and parental involvement. Therefore, rewards function as effective reinforcement for positive learning behavior when applied proportionally, consistently, and contextually according to students’ needs in the learning process.